Robocow Enterprise: Portable Milking Machine /Mohammad Kamaruzaman Shamsuddin ...[et al.] - Shamsuddin, Mohammad Kamaruzaman; Mohd Nordin, Ahmad Tarmizi; Aidil, Muhammad Adry Shah; Mohamed, Ahmad Fadhil; Rosli, Ariff Adha (2016)
This endeavor is expected to flourish and become more profitable in the long run. Furthermore, the product that this company manufactures has an unlimited potential for innovation.